Turbulence transport within the Heliosphere. (15th January 2015) - Adhikari, L; Zank, G P; Bruno, R; Telloni, D; Hunana, P; Dosch, A
Abstract: This work continues the investigation of turbulence transport throughout the supersonic solar wind initiated in Zank et al 1996 [27] and Zank et al 2012 [20]. [20] developed a system of six coupled transport equations that describe the transport of energy corresponding to forward propagating (g) and backward propagating modes (f), the residual energy ( ED ), and the correlation lengths corresponding to forward propagating modes (λ − ), backward propagating modes (λ + ), and the correlation length (λ D ) for residual energy. These models can be applied to both sub-Alfvénic (such as the lower corona) and super-Alfvénic (e.g., supersonic solar wind and inner heliosheath) flows. The correlation lengths calculated from our model are in good agreement with those observed. The evolution of related parameters is also calculated from 0.29 AU to 5 AU.